Tantangan Dan Peluang Dalam Implementasi Kebijakan Lingkungan Di Pemerintahan Daerah - Widiasih, Suprapti; Julina, Faizah; Sekarsari, Dini (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2024)
The implementation of environmental policies in local governments faces various complex challenges. One of the main challenges is the limited resources, both at home and abroad in terms of financial and competent human resources. Many local governments have difficulty providing adequate budgets for environmental programs because they compete with other sectors such as infrastructure and health. In addition, the lack of experts in the field of environment is also worsening this situation, hindering the effectiveness of the implementation of the policy that has been formulated. On the other hand, regulatory challenges and coordination between institutions also pose significant obstacles. The inconsistency of regulations between the central and regional governments is often the cause of confusion in implementing policies in the field. Poor coordination between government institutions, both horizontally and vertically, is also the cause of overlapping programs and ineffective policies. This condition is exacerbated by the low level of community participation in the policy-making and implementation process which leads to a lack of support from the community. However, there is a great opportunity in efforts to implement environmental policies that can be optimized by local governments. The use of technology and innovations in environmental management, such as system geospatial information and real-time air quality monitoring, can improve the efficiency and effectiveness of environmental programs. In addition, partnerships with the private sector and non-governmental organizations can also be a catalyst for capacity building and financing. The existence of global awareness of the importance of environmental sustainability also opens up opportunities for local governments to obtain international support in the form of funds and technical for environmental projects.